2022
DOI: 10.1017/jns.2022.69
|View full text |Cite
|
Sign up to set email alerts
|

Salt consumption and mortality risk in cirrhotic patients: results from a cohort study

Abstract: Since conducting a long-term randomised clinical trial is not logical and feasible to find the optimum dosage of salt intake in patients with cirrhosis, cohort studies are the best design to assess the long-term effects of dietary salt on the survival of cirrhotic patients. This cohort study aimed to evaluate the association between dietary intake of salt and mortality risk in cirrhotic patients. The present study was designed as a cohort in three referral hospitals in Iran in 2018. One hundred and twenty-one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…A recent cohort study from Iran reported that high dietary intake of salt (9.5–15 g/d) increases the rate of mortality in patients with cirrhosis (HR 2.26). Moreover, moderate salt restriction (3–5 g/d), as compared to salt elimination, decreases the risk of death (HR 0.72)[ 38 ].…”
Section: Salt and Cirrhosis: Important Issuesmentioning
confidence: 99%
“…A recent cohort study from Iran reported that high dietary intake of salt (9.5–15 g/d) increases the rate of mortality in patients with cirrhosis (HR 2.26). Moreover, moderate salt restriction (3–5 g/d), as compared to salt elimination, decreases the risk of death (HR 0.72)[ 38 ].…”
Section: Salt and Cirrhosis: Important Issuesmentioning
confidence: 99%